Identification of a Hydroxyproline Transport System in the Legume Endosymbiont Sinorhizobium meliloti - Allyson M. MacLean; Catharine E. White; Jane E. Fowler; Turlough M. Finan (Molecular Plant-Microbe Interactions, 2009)
Hydroxyproline-rich proteins in plants offer a source of carbon and nitrogen to soil-dwelling microorganisms in the form of root exudates and decaying organic matter. This report describes an ABC-type transport system dedicated to the uptake of hydroxyproline in the legume endosymbiont Sinorhizobium meliloti. We have designated genes involved in hydroxyproline metabolism as hyp genes and show that an S. meliloti strain lacking putative transport genes (ΔhypMNPQ) is unable to grow with or transport trans-4-hydroxy-l-proline when this compound is available as a sole source of carbon. Expression of hypM is upregulated in the presence of trans-4-hydroxy-l-proline and cis-4-hydroxy-d-proline, as modulated by a repressor (HypR) of the GntR/FadR subfamily. Although alfalfa root nodules contain hydroxyproline-rich proteins, we demonstrate that the transport system is not highly expressed in nodules, suggesting that bacteroids are not exposed to high levels of free hydroxyproline in planta. In addition to hypMNPQ, we report that S. meliloti encodes a second independent mechanism that enables transport of trans-4-hydroxy-l-proline. This secondary transport mechanism is induced in proline-grown cells and likely entails a system involved in l-proline uptake. This study represents the first genetic description of a prokaryotic hydroxyproline transport system, and the ability to metabolize hydroxyproline may contribute significantly toward the ecological success of plant-associated bacteria such as the rhizobia.